2014
DOI: 10.3109/08923973.2014.884136
|View full text |Cite
|
Sign up to set email alerts
|

Leucoagglutinating phytohemagglutinin: purification, characterization, proteolytic digestion and assessment for allergenicity potential in BALB/c mice

Abstract: Red kidney bean (Phaseolus vulgaris) is consumed worldwide as a vegetarian protein source. But, at the same time the allergenicity potential of red kidney bean is a matter of concern. This study is aimed towards purification, characterization, thermal stability, proteolytic digestion and allergenicity assessment of one of the clinically relevant allergens of red kidney bean. The purification of red kidney bean allergic protein was carried out with the help of column chromatography, IgE immunoblotting and rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 32 publications
(32 reference statements)
0
12
0
Order By: Relevance
“…The ratio of pepsin to lectin (native, preheating or demetallized lectin) used in the SGF assay was 13:1 (w/w) , such that there were 10-32 units of pepsin activity per lg test protein according to the United States Pharmacopoeia. As reported in previous studies, there was a higher repeatability (91% agreement) when a ratio of 10 units of pepsin activity per lg test protein was used in the digestion reaction at pH 1.2 (Thomas et al, 2004), and the weight ratio of 13:1 has been successfully utilised in the in vitro digestion assay of PHA in SGF to measure the relative digestibility of lectin (Kumar, Sharma, Das, Jain, & Dwivedi, 2014). Next, 10 ll of the test protein solution (5 mg/ml containing 2.0 mg/ml NaCl) were added to each of the SGF solution (200 ll, preheated to 37°C) in a water bath to start the digestion reaction.…”
Section: In Vitro Digestion Assaymentioning
confidence: 84%
See 1 more Smart Citation
“…The ratio of pepsin to lectin (native, preheating or demetallized lectin) used in the SGF assay was 13:1 (w/w) , such that there were 10-32 units of pepsin activity per lg test protein according to the United States Pharmacopoeia. As reported in previous studies, there was a higher repeatability (91% agreement) when a ratio of 10 units of pepsin activity per lg test protein was used in the digestion reaction at pH 1.2 (Thomas et al, 2004), and the weight ratio of 13:1 has been successfully utilised in the in vitro digestion assay of PHA in SGF to measure the relative digestibility of lectin (Kumar, Sharma, Das, Jain, & Dwivedi, 2014). Next, 10 ll of the test protein solution (5 mg/ml containing 2.0 mg/ml NaCl) were added to each of the SGF solution (200 ll, preheated to 37°C) in a water bath to start the digestion reaction.…”
Section: In Vitro Digestion Assaymentioning
confidence: 84%
“…It is noted that most food allergens are stable in SGF for the full 60-min reaction period (Astwood et al, 1996;Fu et al, 2002;Grozdanovic et al, 2014). A previous study (Kumar et al, 2014) showed that the PHA-L was resistant to pepsin up to 60 min, suggesting that lectin may cause food allergy by provoking the immune system after reaching the intestinal mucosa. Similar SGF-digestion pattern was also obtained in the investigation of Con A (Takagi et al, 2003).…”
Section: The Stability Of Native Lectin In Simulated Digestion In Vitromentioning
confidence: 95%
“…The time of 40 min was enough for the entire inactivation process of soybean protease inhibitors and lectins (Brune et al, 2010). Kumar et al (2014) showed that the leucoagglutinating phytohemagglutinin (PHA-L) was resistant to pepsin for up to 60 min.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, one of the major causes of poor nutritional value of seeds is the resistance of some storage proteins to proteolysis (World Health Drganization, 2002). Moreover, in the gastric digestive system, most food allergens tend to be stable and capable of reaching and passing through the intestinal mucosa in order to provoke the immune system by triggering an IgE-mediated allergic response (Dimitrijevic et al, 2010;Kumar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this class of protein showed a broad spectrum function that has been described as a new trypsin inhibitor (Mandal et al, 2002). Additionally, the immune system is sensible to the most food allergens that are stable and have the capacity to reach the intestinal mucosa and than release an IgE-mediated allergic response (Dimitrijevic et al, 2010;Kumar et al, 2014;De Angelis et al, 2017).…”
Section: Anti-nutritional Factors and Digestibility Of Protein In Caymentioning
confidence: 99%